First exploration of freestanding and flexible Na2+2xFe2−x(SO4)3@porous carbon nanofiber hybrid films with superior sodium intercalation for sodium ion batteries. Issue 38 (20th September 2016) - Yu, Tiantian; Lin, Bo; Li, Qiufeng; Wang, Xiaoguang; Qu, Weili; Zhang, Sen; Deng, Chao
Abstract : A freestanding Na2+2 x Fe2− x (SO4 )3 @PCNF hybrid film introduces a highly-efficient strategy for the mass-production of high-performance cathodes for SIBs. Abstract : The design of a freestanding electrode is the key to the development of energy storage devices with superior electrochemical performance and mechanical durability. Herein, we propose a highly-scalable strategy for the facile synthesis of a freestanding alluaudite Na2+2 x Fe2− x (SO4 )3 @porous carbon-nanofiber hybrid film, which is used as a self-supported and flexible electrode for sodium ion batteries. By the combined use of electrospinning and electrospraying, the freestanding hybrid film is constructed in the form of sulfate nanoparticles enwrapped in highly porous graphitic-like carbon-nanofibers. The multimodal porous architecture of the freestanding hybrid film ensures its superiority in mechanical flexibility and structural stability during repeated electrochemical processes, which meets the long-standing challenge of practical application. Moreover, both the highly conductive and porous framework and the nanoscale particles are favorable for promoting fast electron/ion transport capability. Compared with other carbon based supports such as graphene (GA), carbon nanotubes (CNTs) and active carbons (ACs), the flexible carbon nanofiber shows better interaction with electrochemical active materials and superior electrochemical properties. It retains over 95% of the capacity after five hundred cycles at alternate rates of 40C and 5C, which demonstrates the superior ultralong time and high-rate cycling capability. Therefore, the present work provides a facile and highly scalable strategy for the design and fabrication of high-performance freestanding sulfate cathodes for advanced sodium ion batteries.